Propagação in vitro da gabirobeira (Campomanesia spp.) - Maldonado, Alirio Coromoto Daboin (2014)
Gabirobeira is a typical fruit from the Brazilian Savannah presenting social, economic and commercial importance; however, its preservation is threatened by the expansion of agriculture and by predatory extractivism. This study proposes a protocol for in vitro propagation of the species. Several experiments were done from 2010 to 2013, using fruits harvested from twenty selected gabirobeira shrubs on the farm ―Água Limpa‖ at the Federal University Uberlândia - MG. In Chapter1, theoretical and general information about the species were compiled. Chapter 2presentes the effects of seed disinfestation on in vitro germination, comparing several concentrations of sodium hypochloride, associated with ethanol (70%) and with the fungicide methyl thiophanate (1 g L-1), in MS medium supplemented with 1.5% sucrose and BAP (1 mg L-1). Seed disinfestation allowed in vitro establishment of the fruit shrub and, after growth for 10 days the least contamination was observed (4.80%), with greatest germination (94%) after treatment with increasing concentrations of sodium hypochloride, up to 3.50%. Thirty days after seeding in the medium 100% germination and no contamination were observed with sodium hypochloride concentrations of up to 3.33%. Chapter 3 evaluates the effects of different anti-oxidants during micropropagation of nodal segments of gabirobeira obtained from seedlings germinated in vitro. Oxidation (%) was evaluated 15 days after transfer to the different media and the number of sprouts 15 days later. The following results were observed: There were no significant differences among the treatments for oxidation, and the medium MS + PVP was the least oxidant. Significant differences among the treatments with anti oxidant substances and lighting were observed for the number of sprouts, and the treatments MS + PVP, MS + activated charcoal, MS + ascorbic acid and MS in the dark were similar to each other. Therefore, treatments containing PVP and activated charcoal in MS medium are the best option to control oxidation and generate the greatest number of sprouts in gabirobeira explants for in vitro propagation. Chapter 4 evaluated, 60 days after in vitro introduction, gabirobeira seedling development. Collected data indicate that the effect of sodium hypochloride (3.60%) in synergy with ethanol and fungicide, coupled to the presence of BAP (1 mg L-1) in MS medium, positively affected the physiological establishment of the seedlings, as shown by the number of sprouts, leaves and seedling height (1.4, 5.52, and 17,67 mm, respectively), regardless of immersion time. Chapter 5, determined the best combination MS culture medium, in combination with BAP, to select the explant with the greatest number of sprouts, with no oxidation. According to the data, it can be concluded that BAP at 0.5 mg L-1 resulted in greater growth and sprout development in nodal segment explants, while greater concentrations of the hormone resulted in explant oxidation. Diluted MS medium to 1/4 (25% of the base MS medium) was more effective for in vitro propagation of gabirobeira nodal segments.